Ruthenium Assemblies for CO2 Reduction and H2 Generation: Time Resolved Infrared Spectroscopy, Spectroelectrochemistry and a Photocatalysis Study in Solution and on NiO - Cerpentier, Florian J. R.; Karlsson, Joshua; Lalrempuia, Ralte; Brandon, Michael P.; Sazanovich, Igor V.; Greetham, Gregory M.; Gibson, Elizabeth A.; Pryce, Mary T. (Frontiers in Chemistry, 2021)
Two novel supramolecular complexes RuRe ([Ru(dceb)2(bpt)Re(CO)3Cl](PF6)) and RuPt ([Ru(dceb)2(bpt)PtI2](PF6)) (dceb = diethyl[2,2’-bipyridine]-4,4’-dicarboxylate, bpt = bipyiridine-1,2,4-triazole) were synthesized as new catalysts for photocatalytic CO2 reduction and H2 evolution, respectively. The influence of the catalytic metal for successful catalysis in solution and on a NiO semiconductor was examined. IR-active handles in the form of carbonyl groups on the peripheral ligand on the photosensitiser were used to study the excited states populated, as well as the one-electron reduced intermediate species using infrared and UV-Vis spectroelectrochemistry, and time resolved infrared spectroscopy. Inclusion of ethyl-ester moieties led to a reduction in the LUMO energies on the peripheral bipyridine ligand, resulting in localization of the 3MLCT excited state on these peripheral ligands following excitation. RuPt generated hydrogen in solution and when immobilized on NiO in a photoelectrochemical (PEC) cell. RuRe was inactive as a CO2 reduction catalyst in solution, and produced only trace amounts of CO when the photocatalyst was immobilised on NiO in a PEC cell saturated with CO2.